Založení malého podniku - Gabrhelová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá založením cestovní kanceláře orientované na firemní cestování. Na základě teoretických poznatků získaných studiem, praxí v oboru a analýze trhu jsou sestaveny kroky k založení podniku.

The masters´s thesis deals with the establishment of a travel agency focused on corporate travel. The thesis is based od the theoretical knowledge gained through study, practice and market analysis are being taken the steps to set up a business.
Small Company Establishment
Keywords: Podnikatelský plán; cestovní kancelář; corporate travel management; analýza trhu; SLEPT analýza; marketingový plán; finanční plán; SWOT analýza; Business plan; travel agency; corporate travel management; market research; SLEPT analysis; marketing plan; financial plan; SWOT analysis